INVESTIGASI PENERAPAN TEORI MANAJEMEN PENDIDIKAN MODERN DALAM PENGAMBILAN KEPUTUSAN DI SEKOLAH ISLAM - Rasya Khairunnida; Dea Sri Rahayu; Leni Nuraeni; Atikah Ainul Faroidh; Nurhayati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to investigate the implementation of modern educational management theory in decision making within Islamic schools, emphasizing the integration of rational based managerial approaches with Islamic values. The research employs a qualitative approach using a library research method through the analysis of relevant and up to date scholarly sources. The findings indicate that the application of modern management, particularly through the POAC framework, has been adapted in the context of Islamic schools by incorporating values such as shura (consultation), amanah (trustworthiness), justice, and public welfare (maslahah). Furthermore, the decision making model does not solely rely on bounded rationality but is also enriched by participatory and spiritual approaches. However, a gap remains between theory and practice, caused by limitations in resources, leadership capacity, an intuition-based work culture, and high administrative demands. Therefore, this study recommends strengthening leadership competencies, developing an Islamic organizational culture, and optimizing data utilization in decision making to achieve more adaptive, professional, and sustainable educational governance.